PERLINDUNGAN HUKUM BAGI PARA AHLI WARIS TERKAIT WASIAT YANG DIBUAT OLEH NOTARIS MELEBIHI KETENTUAN BESARNYA BAGIAN DALAM PERSPEKTIF HUKUM WARIS ISLAM - Reza Rosmeilisa; M. Slamet Turhamun; Felicitas Sri Marniati (Bajang Institute, 2026)
In making a will by a Muslim heir, some are still carried out as the freedom to carry out civil acts as in general, even though the will is made with the help of a notary, problems often arise later (das sein), because this is not in accordance with the contents of Article 195 of the KH I regarding how a will is carried out, in accordance with Islamic provisions, and regulates that a will is only valid if approved by all heirs (das sollen). This is based on two problem formulations, namely: What are the legal consequences of a will made by a Notary and how is the legal protection for heirs related to a will made by a notary that exceeds the provisions on the size of the share in the perspective of Islamic inheritance law. This research was analyzed using the Theory of Legal Consequences according to R. Soeroso and the Theory of Legal Protection according to Djojohadikusumo. The research methodology used is normative legal research, specifically library research or secondary data analysis, utilizing primary, secondary, and tertiary legal materials. The research approach includes statutory (regulatory), case, analysis, analytical, and conceptual approaches. Data collection techniques involve identifying and inventorying positive legal regulations, books, journals, and other legal sources. The legal materials are analyzed using systematic legal interpretation and the legal construction method. From the research results, it can be concluded that the legal consequences of a Will made by a Notary exceeding the provisions in the form of non-compliance with sharia principles give rise to ethical and administrative consequences so that it has the potential to be cancelled by the court. Regarding legal protection for heirs, if a legal act occurs in the form of a will that violates Islamic inheritance provisions, then the will is cancelled and redistribution is according to the main provisions of the heir's share, and the heirs can file a lawsuit with the court to cancel and adjust the contents of the will.